Korelasi Peningkatan Kadar Trigliserida Terhadap Pembentukan Small Dense LDL Pada Pasien Diabetes Melitus Tipe 2 - Musyarrafah Musyarrafah; Christiana Lethe; Joko Widodo (Halu Oleo University, 2015)
Type 2 diabetes increases of triglyceride level due to change of Low Density Lipoprotein (LDL)concentrations, with regard to both numbers and sizes of LDL particles. Small, dense LDL particles are more atherogenic than larger, buoyant LDL and that Apo B is more accurate measure than LDL with regard to predicting cardiovascular disease in patient with type 2 diabetes. This study to determine the correlation between elevated of triglyceride concentration to small dense LDL production in patient with type 2 diabetes. This study was cross sectional design. The subject in this study was type 2 diabetes patient with age more than30 years old (n=33). Triglyceride was analyzed by enzymatic-colorimetric method. Small dense LDL production was calculated by ratio of LDL/Apo B <1.2. Data analysis was performed with Spearman test with significance level of 0.05. The result showed that elevated of triglyceride concentration with small dense LDL formation (ratio of LDL/Apo B <1.2) found on 11 (33.4%) patient, while patient with the elevated of triglyceride concentration and non formation of small dense LDL (ratio of LDL/Apo B≥1,2) found on 9 (23.3%) patient. There was significantly correlation (p=0.027, r= -0.385) between the elevated of triglyceride concentration to the small dense LDL production. In conclusion, the elevated of triglyceride concentration lead to formation of small dense LDL in type 2 diabetes patient. Furthermore, LDL/Apo B ratio could be used as standard parameter to predict cardiovascular disease.Keyword: Type 2 diabetes, triglyceride, Apoliprotein B, small dense LDL.